EKSPRESI WAJAH ANAK-ANAK DALAM KARYA SENI LUKIS REALIS - Reza Indra Prasetyo, Drs. Abd. Hafiz, M.Pd, Yasrul Sami, S.Sn., M.Sn. (Serupa The Journal of Art Education, 2017)
Th The purpose of the creation of this final work is to visualize the facial expressions of children of various forms, in the art of realist painting. The method of creation, using the five stages of preparation stage, elaboration stage, synthesis stage, stage of concept realization and completion and exhibition. Using acrylic paint with brushstrokes technique and using colors that match the object. Ten works are made representing a theme that tells of the facial expressions of children. The author's interest in the theme of facial expressions of children because of his innocence. At the time of interacting with others they are expressed in the absence of engineering, because every expression shown is a real response as it is felt.Keywords: Facial Expression, Children, Painting, Realist